Analisis Tindak Tutur Ekspresif dan Direktif dalam Pembelajaran Berdiferensiasi pada Kurikulum Merdeka dalam Kanal Youtube Catatan Guru Muda - Feesya Diva Zafiera; Salma Khairunnisa Anugerah; Jihan Hasna Huwaida; Naura Azifah Zatayumnia; Tara Cantika Candra Satiti; Ervina Gita Pramesti; Asep Purwo Yudi Utomo (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
Differentiated learning videos are learning method videos for educators delivered to students. Pragmatics is the science of language that studies the relationship between language and its context, grammatically or encoded in the structure of language use. In this research, there are expressive speech acts, namely a type of speech act in which the utterance states something or things that the speaker intends to feel, and directive speech acts are speech acts that express the speaker's intentions, which can be realized in the form of pragmatic statements. This article was written using descriptive research, which ultimately attempts to describe the speech spoken by the object, which is in accordance with the actual picture. This research uses a qualitative approach, namely by applying a qualitative descriptive method using data collection techniques, namely listening and note-taking analysis, which then uses collection analysis and matching analysis. This research aims to collect data, explain the data clearly, and analyze the forms of directive and expressive speech acts contained in differentiated videos. Differentiated video is a medium that allows the delivery of messages or information more specifically according to the target audience. Directive speech act analysis involves identifying commands, requests, or instructions given in the video, while expressive speech act analysis focuses on the expression of feelings, opinions, or expressions of emotion in that context. The results of the analysis show variations in the use of directive and expressive speech acts depending on the purpose of communication and audience characteristics. These findings provide insight into how differentiated video is used to achieve diverse communicative goals, including educating, motivating, or influencing audience actions. Based on the results of the analysis of expressive and directive speech acts in differentiated videos, it can be concluded that there were 23 forms of speech acts found. These speech acts consist of 7 expressive speech acts and 16 directive speech acts. The benefits of this research can provide guidance for content creators and communicators in designing and conveying messages effectively in differentiated video contexts by considering various speech acts that are appropriate to the situation and communication objectives.